Предмет: Алгебра,
автор: vp01407
Как решить это уравнение? Помогите.
Приложения:
![](https://files.topotvet.com/i/d50/d50e7cfdb5d8d9d12ccbea91510cb2e8.png)
Ответы
Автор ответа:
0
[2(x - 2) + 3(x - 1) - 3 + (x - 2)²] / [(x - 1)(x - 2)] =
= (2x - 4 + 3x - 3 - 3 + x² - 4x + 4) / [(x-1)(x-2)] =
= (x² + x - 6) / [(x-1)(x-2)] = [(x+3)(x-2)] / [(x-1)(x-2)] = (x+3) / (x-1)
= (2x - 4 + 3x - 3 - 3 + x² - 4x + 4) / [(x-1)(x-2)] =
= (x² + x - 6) / [(x-1)(x-2)] = [(x+3)(x-2)] / [(x-1)(x-2)] = (x+3) / (x-1)
Похожие вопросы
Предмет: Биология,
автор: sandra98068
Предмет: Математика,
автор: davidbulgakov2008
Предмет: Геометрия,
автор: babarykinmaksiv
Предмет: Математика,
автор: lilil2
Предмет: Биология,
автор: Леон656